DESIGN AND MODELING OF DENIM CLOTHES BASED ON TECTONIC APPROACH - Пашкевич, К. Л.; Єжова, О. В.; Пастух, Я. О.; Роготченко, О. О. (Art and Design, 2019)
Research of features of designing of clothes from jeans with elastan fibres on principles of tectonic approach. Complex approach, method of system-structural and morphological analysis of initial object of research with a subsequent synthesis on the basis of findings are used. Collections of modern designers are analysed, the modern tendencies of fashion in making and finishing of jeans fabrics and wares from them are studied, classification of methods of finishing of jeans clothes is developed. The conducted analys is rotined that the modern methods of final treatment and finishing of jeans fabrics is abrasive, sand-blast treatment, mechanical friction, cutting through, laser engraving, production of «dry» jeans, which is arrived at by a modern highly technological equipment, blades, enzymes. The actual finishing of jeans clothes is embroidery, applique, floral decorative pattern, lace, fringe, spangles and strasses, buttons, etc. Research of physical and mechanical properties of jeans fabrics with elastane fibres is conducted: thickness, surface density, force at rupture, elongation at rupture, the interdependence between them are set. Scientific novelty. The assortment of jeans clothes is investigated, the tendencies of fashion, innovations and decorative finishing of jeans wares are certain. The interdependence between physical and mechanical properties of jeans and tectonic form of clothes is studied. Comparing of properties of jeans fabrics with fliselin and without it are executed, on the basis of what the scientifically grounded recommendations are given on the choice of assortment of jeans clothes. Practical significance. The conducted complex of scientific researches on designing of clothes on the basis of tectonic approach and determination of physical and mechanical properties of jeans fabrics is basis for development of recommendations on the choice of jeans fabrics for the models of clothes of different assortment and creation of collection of modern jeans clothes.